Validity of Gapon’s Constant in Predicting Soil Sodicity - Paliwal, K V (Annals of Arid Zone, 2016)
Validity of Garon’s equation to predict ESP of salt affected soils was examined from the available data. Experimental evidences indicate that Gapon’s constant is not constant for all soils and varies with salinity,ESP, anionic composition, soil type, cation exchange capacity weather ability,organic matter and lime content of the soils. Better prediction of exchangeable sodium achieved with Gapon’s equation by using the kg value obtained for presentage can be representative soils involving similar saline-sodie conditions. Merits and demerits of Gapon’s equation have been discussed.